The Impact of Digital Research: Thinking about the MARK16 Project - Clivaz, Claire (Open theology, 2019)
This article presents the challenges of developing Humanities research in a digital environment in relation to a New Testament test-case: the MARK16 project. The first section argues that virtual research environments (VREs) have become an excellent milieu in which to develop a digitized research project based on collaborative work. The second section presents an overview of VREs and digital projects on the New Testament. The third section demonstrates the ways in which the MARK16 project participates in the development of VREs and fosters new modes of engaging material in digitized NT research.